GAYA KOMUNIKASI WAKIL KETUA PARTAI GERINDRA EDHY PRABOWO - Suhaeri Suhaeri; Estu Bondan (SOURCE : Jurnal Ilmu Komunikasi, 2019)
Gerindra is one of the leading political parties in Indonesia. Edhy Prabowo is known as an influential figure in the Gerindra Party who currently serves as Deputy Chairperson of the Gerindra Party. Communication is very important in human life, communication is in every human activity. The form can be in the form of writing, oral, image, gesture, printed words. The style of communication comes in part of communication activities in general. Communication style can influence the smoothness of the communication process in an organization. Job performance is greatly influenced by the motivation of employees who are high in doing their jobs. Motivation for each person or individual is different. Depending on the impulse that is basis of someone doing something or working. This study aims to determine the communication style of Edhy Prabowoin motivating Prabowo Subianto’s guards. The concepts used in this study include the style communication, organizational communication, and work motivation. The research paradigm use constructivists with a descriptive qualitative  reaserch approach. The subjects of the study were Deputy General of Gerindra Party and Guard Prabowo Subianto. The results of the study revealed that the communication style used by Edhy Prabowo as Deputy Chairperson of the Gerindra Party was a combination of the equalitarian style and the structuring style. In leading the organization Edhy Prabowo also uses a democratic leadership style and implements two way communication.Keyword          : Communication Style and Motivation.